Alcance manual e nível de controle de tronco de lactentes entre 6 e 9 meses de idade : estudo observacional - Greco, Ana Luiza Righetto (2016)
Aims: Identify the level of trunk control (Study 1) and relationship the level of trunk control with the reaching (Study 2) in infants at 6 and 9 months of age. Method: This is an observaciotinal and cross-sectional study. Fifty five healthy infants at 6 – 9 months of age were assessed in Study 1 and thirty one healthy infants were assessed in Study 2. The level of trunk control was assessed by Segmental Assessment of Trunk Control (SATCo). The motor development was assessed by Alberta Infant Motor Scale (AIMS). The reaching was assessed by kinematic analysis. During this assessment, the infants were seated in a baby chair reclined. A toy was presented at his/her midline within reaching distance for 2 minutes. The variables analyzed were: frequency uni and bimanual, trunk of support frequency in the chair, grasping and trunk control level, and kinematic variables: movement duration, peak velocity, mean velocity, deceleration index and movements units. Results: Study 1: There was a significant difference among ages 6 to 8 months (p = 0.001), 6 and 9 months (p = 0.000), 7 and 8 months (p = 0.002), and 7 to 9 months (p = 0.001). Study 2: There was no relationship between the kinematic parameters and trunk control levels at each age. There was a higher frequency with an trunk support for the infants at 6 and 7 months old. At 8 and 9 months, there was a higher frequency ranges performed without trunk support. However, there was not relationship between the trunk control level shown by SATCo and the trunk support in the chair during performance reaching for any age. Conclusion: The infants at 6 and 7 months of age had trunk control in the thoracic level while at 8 and 9 months, infants had full control trunk. Furthermore, it is suggested that the trunk control level is not related with reaching in typical infants aged between six and nine months, possibly because this infants had sufficient trunk control to carry out reaching movements. The infants used medium or no trunk support in the chair of assessment during the carry out reaching movements.